2016
DOI: 10.4172/2153-0637.1000139
|View full text |Cite
|
Sign up to set email alerts
|

A Case-control Study in an Orcadian Population Investigating the Relationship between Human Plasma N-glycans and Metabolic Syndrome

Abstract: Background: Alterations in glycosylation patterns have long been known to reflect changes in cell metabolism. In this study, we investigated the relationship between human N-glycan profiles and metabolic syndrome. Method:Between 2005 and 2011, 2,155 individuals from the Orkney Islands (UK) were recruited and biological material, alongside phenotypic measures were collected. Individual N-glycan profiles were measured in plasma using weak anion exchange high performance liquid chromatography and calibrated hydro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 19 publications
1
2
0
Order By: Relevance
“…'s report may explain the contradictory findings. In contrast, in various large cohort studies using higher‐resolution techniques a reduced fucosylation of diantennary structures in T2D and metabolic syndrome was found, notably, in Caucasians as well as Chinese and Ghanaian populations, even after adjustment for possible confounders including age, sex, and BMI . Consistent results were reported for IgG fucosylation in the same, large T2D case–control cohort as presented here .…”
Section: N‐glycomic Signatures Of Major Human Diseasessupporting
confidence: 87%
“…'s report may explain the contradictory findings. In contrast, in various large cohort studies using higher‐resolution techniques a reduced fucosylation of diantennary structures in T2D and metabolic syndrome was found, notably, in Caucasians as well as Chinese and Ghanaian populations, even after adjustment for possible confounders including age, sex, and BMI . Consistent results were reported for IgG fucosylation in the same, large T2D case–control cohort as presented here .…”
Section: N‐glycomic Signatures Of Major Human Diseasessupporting
confidence: 87%
“…Epidemiologic studies have found that patients diagnosed with metabolic syndrome have an altered N-glycan profile, with some components, including those with seven and eight mannose residues, being positively associated with signs of metabolic syndrome and some inversely (Lu et al, 2011;McLachlan et al, 2016). In this study, BDE-99 reduced Alg12 expression and the relative abundance of mannose in CV but not GF mice, suggesting that a PBDE microbial metabolite could also contribute to these changes.…”
Section: Discussionmentioning
confidence: 52%
“…In addition, total plasma N-glycans have been shown to be associated with risk factors of metabolic syndrome (Lu et al, 2011;McLachlan et al, 2016). The inflammatory role of IgG N-glycans, together with their association with the cardiometabolic risk factors, such as aging , central obesity (Russell et al, 2018), dyslipidemia (Liu et al, 2018a), and hyperglycemia (Ge et al, 2018), leads to the hypothesis of this study that the changes to IgG N-glycan profiles are involved in the pathogenesis of cardiometabolic disease by regulating the inflammatory response.…”
Section: Introductionmentioning
confidence: 94%